Socio-psychological climate of the library staff as a condition for its effective activity - L. A. Trofimova (Библиосфера)
One of the personnel management tasks, including libraries, is the formation of a climate in the work collective. The purpose of the article is to study the state of the socio-psychological climate of the library staff as a factor impacting the efficiency of its activities and to develop recommendations for its evolution. To study the staff of the academic library of Novosibirsk State Technological University (NSTU), the Nemov method for socio-psychological self-assessment of the team, as well as continuous questioning of employees, was used. Based on the results of diagnostics of the socio-psychological climate of the staff of the NSTU academic library, it is shown that the implementation of mentoring practice can contribute to the elimination of the identified shortcomings and to the formation of a more stable socio-psychological climate in the team. In order to reduce the risks of potential conflicts in the team, it is proposed to organize training for the employees of the NSTU scientific library. The results and conclusions obtained can be used in the practical activities of not only the NSTU academic library, but also in any other library with any number of persons in a team.